The Unbearable Sameness of Being and the Logic of Dalit Difference - Anilkumar Payyappilly Vijayan
Delineating three instances of the Dalit differential (Ambedkar’s self-distancing from conservatives and the communists, Chandra Bhan Prasad’s writing and the film discourse from Kerala which equates blackness with essential Dalitness), this article hints at the way in which Dalit discourse is dialecti- cally situated in various historical contexts and discursive systems in order to arrive at the point that untouchability as a political doctrine is not an obsolete project of a bygone era but is very much the built-in mechanism of emancipatory praxis as well as theoretical mediations. As a corollary, the article de-sutures the word untouchability from its unfortunate connection with the body and its visible marker, the skin, and connects it with thought itself. Drawing on Slavoj Žižek’s radical idea that ‘the unbearable is not the difference’, a further argument is put forward: ‘the anti-Dalit’ discursive formation that is happening around us is rooted in what Žižek calls the unbearable, namely the absence of any difference between the self and the projected other.